Medication adherence among persons with coronary heart disease and associations with blood pressure and low-density-lipoprotein-cholesterol - Pedersen, Elisabeth; Primicerio, Raul; Halvorsen, Kjell H.; Eggen, Anne Elise; Garcia, Beate Hennie; Schirmer, Henrik; Waaseth, Marit (European Journal of Clinical Pharmacology, 2022)
Abstract Purpose To describe medication adherence to lipid-lowering drugs (LLDs), antihypertensive drugs, and acetylsalicylic acid (ASA) among persons with coronary heart disease (CHD) and explore its association with low-density-lipoprotein (LDL)-cholesterol, and systolic and diastolic blood pressure. Methods Based on record linkage between the seventh wave of the Tromsø Study and the Norwegian Prescription Database, medication adherence was calculated as the proportion of days covered (PDC) for persistent prevalent users in the period of 365 days before the attendance date. Multivariable linear regression models were used to assess the association between systolic and diastolic blood pressure and medication nonadherence to antihypertensive drugs, age, sex, lifestyle, body mass index (BMI), current and previous diabetes, and between LDL-cholesterol and medication nonadherence to LLDs, age, sex, lifestyle, BMI, and current and previous diabetes. Results Mean PDC was 0.94 for LLDs and antihypertensive drugs and 0.97 for ASA. Among persons with PDC ≥ 0.80 for LLDs, 12.0% had an LDL-cholesterol < 1.8 mmol/L. Blood pressure < 140/90 mmHg (< 140/80 mmHg if diabetes patient) was reached by 55.1% of those with a PDC ≥ 0.80 for antihypertensive drugs. Adherence to LLDs was associated with lower LDL-cholesterol, while neither systolic nor diastolic blood pressure was associated with adherence to antihypertensive drugs. Conclusion Adherence to antihypertensive drugs, LLDs, and ASA among persons with CHD were high despite low achievement of treatment goals for blood pressure and LDL-cholesterol. There was a statistically significant association between adherence to LLDs and LDL-cholesterol, but not between adherence to antihypertensive drugs and blood pressure.